A Middle Bronze Age Roundhouse at Beauly Substation, Beauly, Inverness-shire (Scottish Historical and Archaeological Internet Reports, 2026)
AOC Archaeology Group undertook archaeological mitigation fieldwork in advance of substation reinforcement works at Beauly Substation, Beauly, Inverness-shire, Highland (centred on NGR: NH 5036 4455). Excavation identified the remains of a roundhouse of Middle Bronze Age date, comprising a turf and stone bank and an internal post setting. A small assemblage of macroplant and charcoal was recovered from the site, as well as two saddle querns, two flint artefacts, and sherds of prehistoric pottery. The site lies within a complex prehistoric landscape that has undergone intensive modern archaeological investigation. Combined with the present works, this has revealed a landscape consisting of domestic and agricultural elements comprising roundhouses and associated field systems, as well as funerary elements such as cists and burial cairns. Beauly provides an informative landscape case study, which can be compared with similar sites in the Scottish Highlands such as Navidale, Lairg, and Dalchork. NHRE ID: 376515